Polyethylene glycol-magnetite composite encapsulated concrete as a thermal energy storage - Achmad M.S. Sebayang; Syahrul Humaidi; Timbangen Sembiring; Anggito P. Tetuko; Erna Frida; Perdamean Sebayang; Martha Rianna; Amdy Fachredzy; Muhammad A.H. Nabawi; Muhammad Fauzi; Eko A. Setiadi; Nining S. Asri; et al. (Results in Materials)
Polyethylene glycol (PEG), as an organic PCM, has great potential for Thermal Energy Storage (TES) applications, particularly in concrete. PEG has high latent heat, wide transition temperature range, thermal stability, and biocompatibility. However, the low thermal conductivity of PEG is a disadvantageous. In this study, magnetite (Fe3O4) was added as a filler to improve the thermal performance of PEG. The synthesis and homogenization were performed via sonication and magnetic stirring. XRD characterization showed that the PEG-magnetite composite did not undergo any chemical reaction or form new phases. The addition of 45 vol% of magnetite increased the magnetization saturation to 29.84 emu/g and decreased the latent heat to 79.73 %. Thermogravimetric analysis showed an increase in the decomposition temperature of up to 18.54 %. The PEG85 composite sample, with a latent heat of 128.06 J/g and thermal conductivity of 0.407 W/m⋅°C is the most suitable for TES. The novel configuration of tubes encapsulation media to store PEG-magnetite composite improves the capability of the concrete to act as a thermal energy storage.